Odontogenic cutaneous sinus tracts: A clinician's dilemma - Muthu Sendhil Kumaran; Tarun Narang; Sunil Dogra; Sudhir Bhandari (Wolters Kluwer Medknow Publications, 2020)
Background: Odontogenic cutaneous sinus tract (OCST) is one of the rare manifestations of chronic dental infections. Although well reported in literature, it is often misdiagnosed or under diagnosed. Apart from isolated case reports especially in dental literature there is a paucity of comprehensive case series on OCST. Aims and Objectives: We undertook this study to observe the prevalence, clinico epidemiological features and management issues in these patients from a dermatological perspective. Methods: A retrospective study was undertaken analyzing the clinical records of patients registered at our outpatient department (OPD) from 2011 to 2018. Cases with a clinical and radiological diagnosis of odontogenic cutaneous sinus were included in the study. We studied the following variables: frequency, gender, age, localization, morphology, mean time of evolution and treatment response. Results: 21 patients with OCST were identified from our records. Females outnumbered males; patients in the age group between 31-40 years were more commonly affected. Three morphological presentations were noted in the form of flesh-colored dry nodules with sinus, adherent plaques with mucopurulent discharge and ulcer. Posterior set of teeth were commonly affected and mandible was the commonest site for location of sinus. The time taken for appropriate diagnosis in these cases ranged from 7-16 months. Almost all the patients responded to endodontal or root canal treatment and there were no recurrences. Conclusion: A CST of dental origin is often a diagnostic challenge, especially in cases with minimal or no dental symptoms. A thorough skin and dental examination is required for sinuses on the head and neck area with a high index of suspicion for OCST. Most cases respond to conservative, root canal therapy. An early diagnosis can save the patient from unnecessary and ineffective therapies and sometimes surgeries.